The potential of Bacillus strains isolated from the rumen content of dairy cows as natural antibacterial and antioxidant agents for broilers - Sugiharto, S.; Yudiarti, T.; Isroli, I.; Widiastuti, E.; Wahyuni, H.I.; Suprijatna, E. (Diponegoro University, 2018)
The study was conducted to investigate the in vitro antibacterial activity and antioxidant-enhancing effect of Bacillus strains isolated from the rumen content of dairy cows. The antibacterial activity of Bacillus strains was assessed against Escherichia colibased on the agar-well diffusion method. To assess the antioxidant-enhancing effect, the Bacillusstrains was mixed (prepared as multi-strains) and used to ferment herbal medicine waste (HMW). The effect was compared with that of commercial probiotic Bacillus subtilis and non fermented HWM. Results showed that each Bacillus strain was able to inhibit the growth of E. coli. Fermentation with mixed Bacillus strains tended (P=0.07) to enhance the 2,2-diphenylpicrylhydrazyl (DPPH) radicals scavenging activity and total phenolics content of HMW. In contrast, fermentation with commercial Bacillus subtilis tended (P=0.07) to decrease DPPH radical scavenging activity and total phenol of HMW. Fermentation with both Bacillus preparations increased (P<0.05) the contents of crude protein and ash in HMW, while crude fat increased (P<0.05) in HMW fermented with Bacillus subtilis. Fermentation either with Bacillus subtilis or mixed Bacillus strains increased (P<0.05) the fiber content of HMW. In conclusion, Bacillus strains isolated from the rumen content of dairy cows showed antibacterial activity and antioxidant-enhancing effect, therefore, they are potential as feed additive to substitute synthetic antibiotics and antioxidants for broilers raised under tropical conditions.